Ethnological Studies on Visiting Traditions for Preservation Community Culture - Casminih, Casminih (Universitas Pendidikan Indonesia (UPI), 2023)
The tradition is hereditary customs of ancestor that still maintained his presence in the community. One of the traditions of the societies in Indramayu Regency is called